Fundamental Valuation Of HIMBARA Group Stocks Using PBV And PER Approaches - Indah Lestari Anwar; Fitriani Rahim (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to evaluate the fairness of the stock prices of the Association of State-Owned Banks (HIMBARA), consisting of Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), Bank Mandiri, Bank Tabungan Negara (BTN), and Bank Syariah Indonesia (BSI) during the 2021–2025 period. The study uses a descriptive quantitative approach utilizing secondary data in the form of audited annual financial reports and closing stock prices at the end of the year. The analysis was conducted using the Price to Book Value (PBV) and Price to Earnings Ratio (PER) as the main indicators in assessing stock valuation. The results show that BRI and Bank Mandiri are in the fair valuation category. BNI and BTN are classified as undervalued, while BTN also has the lowest PER. On the other hand, BSI exhibits a premium valuation, reflecting high market expectations for the growth of the Islamic banking industry. Hypothesis testing indicates that HIMBARA's stock tendency to be undervalued is only partially valid, while differences in valuation characteristics between BSI and conventional banks are consistently evident. These findings provide a reference for investors in developing investment strategies based on fundamental analysis in the Indonesian banking sector.